Effect of oxygen defects blocking barriers on gadolinium doped ceria (GDC) electro-chemo-mechanical properties. (1st August 2019) - Kabir, Ahsanul; Santucci, Simone; Van Nong, Ngo; Varenik, Maxim; Lubomirsky, Igor; Nigon, Robin; Muralt, Paul; Esposito, Vincenzo
Abstract: Some oxygen defective metal oxides, such as cerium and bismuth oxides, have recently shown exceptional electrostrictive properties that are even superior to the best performing lead-based electrostrictors, e.g. lead-magnesium-niobates (PMN). Compared to piezoelectric ceramics, electromechanical mechanisms of such materials do not depend on crystalline symmetry but on the concentration of oxygen vacancy ( V O ⋅ ⋅ ) in the lattice. In this work, we investigate for the first time the role of oxygen defects configuration on the electro-chemo-mechanical properties. This is achieved by tuning the oxygen defects blocking barrier density in polycrystalline gadolinium doped ceria with known oxygen vacancy concentration, Ce0.9 Gd0.1 O2-δ, δ = 0.05. Nanometric starting powders of ca. ∼12 nm are sintered in different conditions, including field assisted spark plasma sintering (SPS), fast firing and conventional method at high temperatures. These approaches allow controlling grain size and Gd-dopant diffusion, i.e. via thermally driven solute drag mechanism. By correlating the electro-chemo-mechanical properties, we show that oxygen vacancy distribution in the materials plays a key role in ceria electrostriction, overcoming the expected contributions from grain size and dopant concentration. Graphical abstract: Image 1